The Soul of the Mystical Body: the role of social relationships in the conflict between Carmelite members in Recife in the 18th century: o papel das relações sociais no conflito entre irmãos carmelitas no Recife setecentista - Queiroz, Rafael Lima Meireles de (Temporalidades, 2020)
This paper aims to conduct a survey about the social profile of the members of the First and Third Orders of the Carmo from Recife who were involved in a conflict over the number of times the funeral bells from the Church of the First Order would ring after the death of a lay brother. To this end a cross-sectional analysis of the epistolary documentation of the Third Order of the Carmo from Recife was chosen, crossing their information with other documents like patents, jobs and official notes requests as well as excerpts and transcriptions present in historiographical works. The analysis aims to expose the people involved in the controversy and their relationship networks emphasizing the importance of the distinct “human resource”, namely, those people who had the ability to exert a certain degree of influence before others in society. As a result, it is possible to identify the social profile of the members of the First and Third Orders involved in the conflict and therefore better understand devotion as a means of integration and social conditioning, that in a way is still present today.